Analysis of Moral Disengagement as a Modulating Factor in Adolescents’ Perception of Cyberbullying - Cuadrado-Gordillo, Isabel; Fernández-Antelo, Inmaculada (Frontiers in Psychology, 2019)
There have been various studies establishing a relationship between moral reasoning and the perpetration of cyberbullying, but very few analysing either the moderating role played by moral disengagement in how both aggressor and victim perceive cyberbullying, or the repercussions of this moderation for the determination of the prevalence of the problem and for the design of prevention programs. The present study examines the relationship between moral disengagement, moral identity, and how victims of this type of abuse perceive cyberbullying. The participants were 1912 adolescents (51% women) from Extremadura (Spain) of ages from 14 to 18 years. They completed three questionnaires addressing perception of cyberbullying, moral disengagement, and moral identity. Factorial, structural, correlation, and hierarchical multiple regression analyses were used to construct their perceptual structure of cyberbullying. These analyses showed the influence of their different levels of moral disengagement on those perceptions, and the moderating role that moral identity plays in the direct and indirect relationships between moral disengagement and the perception of cyberbullying. They revealed, on the one hand, the key and the subsidiary criteria victims use to classify some given cybernetic behaviour as a case of cyberbullying, and, on the other, that the victims' levels of moral disengagement explain both the justifications they resort to in order to interpret occurrences of cyberbullying and their shifting or spreading of responsibility onto others. Finally, the results can be a key element in the design of effective psychological interventions aimed at improving adolescents' moral identity in situations of cybernetic victimization.